Sovereign Wealth Fund Asset and Liability Management by Rastin Banking Financial Instruments (Rastin Certificates and Rastin Swap Bonds) - Bidabad, Bijan (American Finance & Banking Review, 2019)
Low rate of return of National Development Fund (NDFI) resources and the concern regarding Sovereign Wealth Funds (SWFs) motivations and incentives to distort financing toward those investments and companies that are influenced by different political pressure groups and other types of corruptions are important problems with these funds.We try to propose a different financing procedure by using Rastin Banking mechanism and standards to fulfill both non-usury financial operations and fruitful supervised investments. This goal is achieved through Rastin Profit and Loss Sharing (PLS) system through Rastin Certificates financial instruments. Moreover, the governments operationally construct SWFs to use their surplus resources of the prosperity period in recession and crises years. We also show that Asset and Liability Management (ALM) of SWFs can be done by using Rastin Swap Bonds (RSBs) that are other Rastin Banking financial instruments.The proposed procedures positively improve NDFI regarding corruption reduction, supervision, preventing usury, availability of resources, funds stability, transactable instruments, operational ALM, rate of return, risk of bad loans, outstanding claims and transparency.